While solving a Recurrence Relation, I got stuck at some Logarithmic equation.For this i have to prove

$$\ln \,\ln (n^{\frac{1}{2^{k}}})=\ln\,\ln\,(n)-k\,\ln 2$$

My Approach

$$\ln \,\ln (n^{\frac{1}{2^{k}}})=\frac{1}{2^{k}}*\ln \,\ln(n)$$

if i convert $2^{k}$ to $k\,\ln\,2$ ,then

$$\ln \,\ln (n^{\frac{1}{2^{k}}})=\frac{\ln \,\ln(n)}{k\,\ln\,2}$$ $$=\ln\,\ln\,(n)-k\,\ln 2$$

but i am not getting how to get

$2^{k}$ to $k\,\ln\,2$ Please help me out!


$\ln \,\ln (n^{\frac{1}{2^{k}}})=\ln [(\frac{1}{2^{k}})\ln(n)] = \ln({2^{-k}}) + \ln(\ln n) = -k \ln2 + \ln(\ln n)$


You can't turn $2^k$ into $k\ln 2$ since it is not true, for example, if $k = 1$, then $2^k = 2 \neq \ln 2 = k\ln 2$.

Your mistake is $$\ln\ln(n^{1/2^k})= \frac 1{2^k}\ln\ln n.$$

You can't ignore that there are two logarithms here and $\ln\ln$ doesn't follow the same rules as $\ln$. What you can do is what ab123 did in their answer:

$$\ln\ln(n^{1/2^k})= \ln\left(\frac 1{2^k}\ln n\right)$$ and then use that $\ln(xy) = \ln x + \ln y$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.